Topical Delivery of Niacinamide to Skin Using Hybrid Nanogels Enhances Photoprotection Effect - Renata Basto; Raquel Andrade; Cláudia Nunes; Sofia A. Costa Lima; Salette Reis (MDPI AG, 2021)
Niacinamide (NIA) has been widely used in halting the features of ageing by acting as an antioxidant and preventing dehydration. NIA's physicochemical properties suggest difficulties in surpassing the barrier imposed by the stratum corneum layer to reach the target in the skin. To improve cutaneous delivery of NIA, a hybrid nanogel was designed using carrageenan and polyvinylpyrrolidone polymers combined with jojoba oil as a permeation enhancer. Three different types of transethosomes were prepared by the thin-film hydration method, made distinct by the presence of either an edge activator or a permeation enhancer, to allow for a controlled delivery of NIA. Formulations were characterized by measurements of size, polydispersity index, zeta potential, encapsulation efficiency, and loading capacity, and by evaluating their chemical interactions and morphology. Skin permeation assays were performed using Franz diffusion cells. The hybrid hydrogels exhibited robust, porous, and highly aligned macrostructures, and when present, jojoba oil changed their morphology. Skin permeation studies with transethosomes-loaded hydrogels showed that nanogels per se exhibit a more controlled and enhanced permeation, in particular when jojoba oil was present in the transethosomes. These promising nanogels protected the human keratinocytes from UV radiation, and thus can be added to sunscreens or after-sun lotions to improve skin protection.